Stylistic processes in Victor Giudice's "Oz gueijos" - Santos, Acácio Luiz (2009)
This article investigates the stylistic technics in Victor Giudice's short story "Oz gueijos", emphasizing: parodic processes; neologism and humour; voicing of voiceless consonants; crosslines; vicious society; and carnival.